Rationale and Design of EMPOWER, a Pragmatic Randomized Trial of Automated Hovering in Patients with Congestive Heart Failure - Mehta, Shivan J (Circ Cardiovasc Qual Outcomes, 2019)
BACKGROUND: Congestive heart failure (HF) is a major cause of morbidity, mortality, and cost. Disease management programs have shown promise, but lack firm evidence of effectiveness and scalability. We describe the motivation, design, and planned analyses of EMPOWER, a randomized clinical trial of an innovative intervention incorporating behavioral economic principles with remote monitoring technology embedded within a health care system. METHODS AND RESULTS: EMPOWER is an ongoing, pragmatic, randomized clinical trial comparing usual care to an “automated hovering” intervention that includes patient-level incentives for daily weight monitoring and diuretic adherence combined with automated feedback into the clinical care pathway, enabling real-time response to concerning clinical symptoms. Identification of eligible patients began in May 2016, and implementation of the intervention is feasible. Trial processes are embedded into existing clinical pathways. The primary outcome is time to readmission for any cause. Cost-effectiveness analyses are planned to evaluate the health care costs and health outcomes of the approach. CONCLUSIONS: The EMPOWER trial incorporates leading edge approaches in human motivation, derived from behavioral economics, with contemporary technology to provide scale and exception handling at low cost. The trial is also implemented within the naturalized environment of a health system, as much as possible taking advantage of the existing journeys of patients and workflows of clinicians. A goal of this pragmatic design is to limit resource utilization, and also to test an intervention that would need minimal modification to be translated from research into a new way of practice.